The labyrinth of mirrors - Blesa, Túa (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
In Leopoldo M.a Panero’s poetry the mirror motif occurs frequently and serves to express a variety of themes. Thus, there is the catoptric mirror, the Carrollian mirror -a doorway into another world- which occurs with higher frequency than the former type and, of yet more frequent occurrence still, the double mirror. At the same time, this latter type of mirror becomes one in the poems to the WilIiam Wilson of Poe, or it declares the absence of reflection, linked to the lack of a name, or it presents on its surface other faces, which is to say it refers to a splitting off, a search for identity. Finally, attention is drawn to the very many images of dismembered figures in the poetry of Panero and these are characterized as fantasies of the "corps morcelé", as Jacques Lacan describes the way the body looks prior to the "stade du miroir".